ANALYSIS OF THE IMPACT OF LEACHATE ON THE QUALITY OF GROUNDWATER AND RIVER WATER IN PUTRI CEMPO LANDFILL IN MOJOSONGO SURAKARTA INDONESIA - Dwi ASTUTI; ANNISA MAYRA; ENDAH LARASATI; HADID AMIRUL ARIFIN (CV KULTURA DIGITAL MEDIA, 2020)
Leachate which is the result of seepage from waste contains high organic pollutants. Therefore, leachate water needs to be treated first before disposal so as not to pollute the environment. Meanwhile, the leachate from the Putri Cempo landfill (TPAS) Mojosogo is discharged into the environment without being treated first because the existing installation is no longer functional. The general objective of this research plan is to analyze the impact of leachate from the Putri CempoMojosongo landfill (TPAS) on the quality of groundwater and river water. The specific objectives of this study were to measure the quality content of leachate water from TPAS Putri CempoMojosongo, to measure groundwater quality content (observation well-water), to measure river water quality before contamination with leachate water, to measure river water quality after contamination with leachate water, and to measure ground water quality of residents at a distance of 0-75 meters TPA; 76-150 meters; 156-225 meters; 225-300 meters; 301-375 meters; and 376-450 meters. This type of research is observational research with measurements and direct observations into the field. Water sampling is carried out by considering the criteria for pollutant sources and the distance of the pollution. The required amount of sample water is taken based on the calculation of the volume of sample requirements. The types of data used include primary and secondary data. Leachate samples were taken from the trenches along the TPAS because the leachate storage pool was not functioning. Groundwater sampling was taken from the closest observation well water to the TPAS, while river water sampling was carried out at a distance of 50 m before and 50 m after the outlet. Sample examination was carried out at the Yogyakarta Center for Environmental Health and Disease Control Engineering. The results of this study indicate that the quality of leachate exceeds the standards for parameters BOD, COD, and TSS. The quality of river water still exceeds the quality standard both before and after being contaminated with leachate water. As for the water quality of observation wells 1 and 2, the conditions are still in accordance with the standards for all parameters, but in the resident wells in each 75meters distance there are still quality parameters that exceed the standard. The parameters include turbidity, organic matter, Mn, and NO3. From these results, the leachate should be treated before disposal so that it does not pollute the surrounding environment.